2016
DOI: 10.31234/osf.io/7xjd9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zooming into Real-Life Extraversion – How Personality and Situation Shape Sociability in Social Interactions

Abstract: What predicts sociable behavior? While main effects of personality and situation characteristics on sociability are well established, there is little evidence for the existence of person-situation interaction effects within real-life social interactions. Moreover, previous research has focused on self-reported behavior ratings, and less is known about the partner's social perspective, i.e. how partners perceive and influence an actor's behavior. In the current research, we investigated predictors of sociable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…We used data from the first wave of the longitudinal Personality and Interpersonal Roles Study (PAIRS; Vazire et al, 2017). Other manuscripts have used the ESM personality state variables (Beck & Jackson, 2018;Breil et al, 2018;Finnigan & Vazire, 2017;Wilson, Harris, & Vazire, 2015;Wilson, Thompson, & Vazire, 2016) and other variables from this dataset (Colman, Vineyard, & Letzring, 2016;Edwards & Holtzman, 2017;Solomon & Vazire, 2016), but this is the first manuscript that examines within-person associations between self-reported and EAR-coded behavior.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the first wave of the longitudinal Personality and Interpersonal Roles Study (PAIRS; Vazire et al, 2017). Other manuscripts have used the ESM personality state variables (Beck & Jackson, 2018;Breil et al, 2018;Finnigan & Vazire, 2017;Wilson, Harris, & Vazire, 2015;Wilson, Thompson, & Vazire, 2016) and other variables from this dataset (Colman, Vineyard, & Letzring, 2016;Edwards & Holtzman, 2017;Solomon & Vazire, 2016), but this is the first manuscript that examines within-person associations between self-reported and EAR-coded behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, experience-sampling research shows that personality trait measures robustly predict the mean level of self-reported personality in the moment (Fleeson & PERSONALITY AND SOCIAL INTERACTION 29 Gallagher, 2009), including extraverted, agreeable, and neurotic behaviors as reported after engaging in social interactions. In a recent experience-sampling study that extended the considered social perspectives, it could be shown that trait extraversion predicted both selfand interaction partner-reported sociable behavior (Breil et al, 2019). Together with the laboratory studies summarized above, these findings underline that people reliably differ with regard to the interpersonal behaviors they express during social interactions and that these differences are related to people's self-concept (i.e.…”
Section: Differences In Interaction State Levelsmentioning
confidence: 70%
“…We propose that extraversion-the most observable of all traits (Back, in press;McCrae & Costa, 1989)-is most salient in an individual's behavior and corresponding selfperceptions. In previous studies that have used experience-sampling data (Breil et al, 2019;Geukes et al, 2019;Wilson et al, 2015) and ratings of videotaped interactions in unacquainted triads (Morse et al, 2015), extraversion was related to more sociable, friendly, and self-revealing behavior and to less emotion suppression. In addition, extraversion has been associated with perceptions of control in social interactions (Barrett & Pietromonaco, 1997;Cuperman & Ickes, 2009) and being the focus of attention (Sherman et al, 2013).…”
Section: Satisfactionmentioning
confidence: 83%
“…For example, extraversion is likely to affect both (a) how sociably people actually behave and (b) how sociable they perceive themselves to be in a social interaction (e.g., Breil et al, 2019). Likewise, personality can influence the perception of other either (a) by affecting the individual's general tendency to perceive another person's behavior or (b) by affecting the individual's behavior such as by triggering actual behavior in the interaction partner in a given social interaction (for a similar argumentation, see Back et al, in press).…”
Section: Perceived Social Interaction Behavior: Mediator Of the Intermentioning
confidence: 99%
See 1 more Smart Citation